Hubungan Dukungan Ibu Mertua Dengan Pemberian Air Susu Ibu Eksklusif Pada Bayi Usia 7-12 Bulan - Ni Luh Putu Wahyu Maisa Arisandi; Ni Nyoman Budiani; Ni Wayan Armini (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2020)
Exclusive breastfeeding only in infants for six months, without any additional food. The complete nutritional content in breast milk provides many advantages including perfect physical growth, intellectual development and emotional maturity, although exclusive breastfeeding provides many advantages but exclusive breastfeeding rates are still. One of the success factors of exclusive breastfeeding is mother-in-law's support. The purpose of this study was to determine the relationship of mother-in-law support with exclusive breastfeeding for baby 7-12 months. The methods in this study area was an corelatif analytical study with case control study. The study was conducted in the working area of I Denpasar Barat Primary Health Care. The sample in this study was classified into two groups: 34 case groups and 34 control groups. The sampling technique used is purposive sampling. Data were collected by questionnaire. Data analysis with chi square test. The results of this study indicate that there is a significant relationship between mother-in-law support and exclusive breastfeeding in infants aged 7-12 months (p value 0,01) and OR value 9,39; CI = 2,977-29,600) which means that respondents who received support from their mother-in-law 9,39 times had an opportunity to give exclusive breastfeeding compared to those who did not get support from their mother-in-law. It is expected that health workers can improve counseling and counseling programs about the importance of exclusive breastfeeding to mothers and family members and provide motivation to the mother in the implementation.